(untitled) - Ministry of Planning and Investment (Hà Nội, 2007)
The book inculude: Review of oda flows and their contribution to sedp, 2001-2005; Analysis of oda flows by donors-did donor groups align themselves to sepd 2001-2005?; DAD Vietnam-curent challenges and the road ahead
Keywords: Economic assistance,Technical assistance,Economic assistance; Developing countries; Viet Nam,Viet Nam